Book Review: (Re)Storying human/earth relationships in environmental Education: A reflection on posthumanist pedagogy and relational agency in environmental education - Muhammad Dafa Dwi Andika (Indonesian Reseacher for Language Learning and Teaching, 2026)
This book review explores Kathryn Riley’s Re(Storying) Human/Earth Relationships in Environmental Education: Becoming (Partially) Posthumanist, which offers a posthumanist and new materialist perspective on environmental education. The review summarizes the book’s structure—Inspiring, Performing, and Becoming—and highlights key enactments such as Mindful Walking and Eco-Art Installation. It evaluates the book’s strengths in relational pedagogy and anticolonial praxis, while also noting its theoretical complexity and limited empirical data. Overall, the review recommends the book as a transformative resource for educators seeking inclusive, land-based, and ethically grounded approaches to teaching in the Anthropocene.